The Effectiveness of Merdeka Mengajar Platform towards the Learning of English Reading Comprehension as the Implementation of Independent Curriculum at UPTD SMPN 19 Barru - Hijriani Hijriani; Amaluddin Amaluddin; Siti Hajar Larekeng (Universitas Muhammadiyah Barru, 2024)
This research aims to find out students' reading comprehension abilities before and after being taught using the Merdeka Menagajar Platform. This study used a one-group pretest-posttest design. There isn't any control group. Researchers give pre-tests to students, and then researchers give students treatment of reading comprehension using the Merdeka Mengajar Platform. The sample of this research was seventh-grade students of UPTD SMPN 19 Barru, a total of 21 students. The results show that the average pre-test score of seventh-grade students at UPTD SMPN 19 Barru experienced a significant increase in the post-test after being taught using the Merdeka Mengajar Platform on treatment. The average student score in reading comprehension on the pre-test was 55.00 and on the post-test was 84.29. So there is an increase in students' reading comprehension. This study shows the value of the t-test is higher than t-table values (14,496 >2.09302). The results of the t-test calculation of student learning before and after being taught using the Merdeka Mengajar platform are greater than the t-table. Can it be concluded that the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted? Researchers concluded that the use of the Merdeka Mengajar platform is a learning method that can improve reading comprehension ability in learning English.